2009
DOI: 10.1242/dev.033449
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulatory sequences inAtoh7mediate non-conserved regulatory responses in retina ontogenesis

Abstract: The characterisation of interspecies differences in gene regulation is crucial to understanding the molecular basis of phenotypic diversity and evolution. The atonal homologue Atoh7 participates in the ontogenesis of the vertebrate retina. Our study reveals how evolutionarily conserved, non-coding DNA sequences mediate both the conserved and the species-specific transcriptional features of the Atoh7 gene. In the mouse and chick retina, species-related variations in the chromatin-binding profiles of bHLH transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…In single-cell gene expression-profiling experiments, roughly similar fractions of progenitors expressed Ascl1, Ngn2 or both factors (Trimarchi et al, 2008 (Ohsawa and Kageyama, 2008); each factor (or combination of factors) is instructive for a specific cell fate. This seems unlikely for Ascl1 and Ngn2, as mice deficient in these transcription factors are able to generate all of the seven principal retinal cell types (Akagi et al, 2004;Hufnagel et al, 2010;Skowronska-Krawczyk et al, 2009;Tomita et al, 2000). Alternatively, these factors could bias progenitors towards neural fates.…”
Section: Progenitor Heterogeneity Correlates With Different Fate Outcmentioning
confidence: 99%
“…In single-cell gene expression-profiling experiments, roughly similar fractions of progenitors expressed Ascl1, Ngn2 or both factors (Trimarchi et al, 2008 (Ohsawa and Kageyama, 2008); each factor (or combination of factors) is instructive for a specific cell fate. This seems unlikely for Ascl1 and Ngn2, as mice deficient in these transcription factors are able to generate all of the seven principal retinal cell types (Akagi et al, 2004;Hufnagel et al, 2010;Skowronska-Krawczyk et al, 2009;Tomita et al, 2000). Alternatively, these factors could bias progenitors towards neural fates.…”
Section: Progenitor Heterogeneity Correlates With Different Fate Outcmentioning
confidence: 99%
“…However, whereas the majority of the ATOH7-expressing cells enter the RGC lineage in the chick, only a few percent produce RGCs in the mouse (Prasov and Glaser, 2012;Skowronska-Krawczyk et al, 2009;Yang et al, 2003). Sustained expression of ATOH7 is required during the last cell cycle for cells to enter the RGC lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained expression of ATOH7 is required during the last cell cycle for cells to enter the RGC lineage. In chick, efficient NGN2-mediated activation of Atoh7 transcription, Atoh7 autostimulation and HES5.3-mediated lengthening of the cell cycle increase the proportion of cells that enter this lineage (Chiodini et al, 2013;Skowronska-Krawczyk et al, 2009). However, this still does not result in numbers of RGCs as high as in the macula and fovea (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage tracing studies demonstrated that RPCs expressing either Atoh7 and/or Neurog2 give rise to all seven major cell classes (Ma and Wang, 2006;Feng et al, 2010;Brzezinski et al, 2012). Importantly, Neurog2 directly activates Atoh7 transcription by binding to an evolutionarily conserved E box in the primary Atoh7 retinal enhancer, and in Neurog2 mutants, Atoh7 expression is delayed along with advancement of neurogenesis (Skowronska-Krawczyk et al, 2009;Hufnagel et al, 2010). The individual requirements of Atoh7 and Neurog2 account for those of the Drosophila orthologue, atonal (ato), in the fly eye (Jarman et al, 1993(Jarman et al, , 1994(Jarman et al, , 1995Brown et al, 2001;Wang et al, 2001;Hufnagel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%